Innovation of Physical Education Teaching Mode in Higher Vocational Colleges from The Perspective of Entrepreneurship Quality Education - Jia, Yuzhi (Transactions on Economics, Business and Management Research, 2023)
With the continuous progress of the times, the cause of education is also undergoing continuous reform and innovation, which makes in the teaching activities, the teaching methods of many disciplines have changed to a great extent, and the higher vocational sports discipline is one of them. Because of the continuous deepening of the concept of quality education, some higher vocational colleges have gradually changed their teaching philosophy when carrying out specific teaching activities, and then pay more attention to the overall development of students. In the stage of higher vocational education, sports discipline has a very important position, it can not only effectively improve the students' comprehensive physical quality, but also to a certain extent, improve the students' entrepreneurial quality. Based on this, this paper analyzes the cultivation methods and objectives of entrepreneurship quality of higher vocational college students, hoping to provide some help for the development of related work.